Fatores associados a traços psicopáticos em presidiários homicidas - Zancanaro, João Rodrigo (Universidade do Vale do Rio dos Sinos, 2017)
The crime of homicide has been growing all over the world, and to identify the reasons associated to it is fundamental to its prevention. The psychopathy is a personality disturbance which might bring serious psychological and social dimensions, maybe leading to a criminal and violent behavior, maybe, the homicide. The goal of this study was to investigate psychopathic traits in convict murders (now in closed conditions) at the pen of Passo Fundo and to examine the associated factors. The essay is organized in two empirical studies. The first one is based on a descriptive and exploratory method, in order to know the criminal, social and demographic profile and the history and its links to trauma in the childhood of the prisoners who have committed crime against life, comparing psychopaths and no psychopaths. The second one, is about the relation between childhood traumatic experiences and psychopathic traits of these prisoners. In both studies, the sample is 27 convicted murders. The data were collected using a social and demographic questionnaire; the prisoners’ reports; the Hare Psychopathy Checklist-Revised (PCL-R); the Parental Bonding Instrument (PBI) and the Childhood Trauma Questionnaire (QUESI). The data were analyzed, in numbers, through a descriptive, transversal and correlative statistic and comparing averages and proportions. In a general view, the results show a great number of psychopaths among the interviewed and show, also, the relation between psychopathy and mother’s parental way in the childhood, mainly the maternal control. Although the sample size has made difficult the profile comparative analyses, the study shows some possible associations among social demographic variables and relatives which need a better investigation in the future.
Keywords: Psicopatia; Apego; Trauma; Abuso; Vínculos familiares; Homicídio; Latrocínio; Psychopathy; Social demographic; Parental bonding; Homicide; ACCNPQ::Ciências Humanas::Psicologia